(untitled) (Research, Society and Development, 2021)
Alzheimer is a brain disease that is linked to the patient’s age, in which an understanding of its progression can be favorable to prevent the disease through early intervention. The different mortality rates in the large regions of the country present inequalities in socioeconomic development, requiring more efficient public policies. Hence, this research is a descriptive cross-sectional epidemiological study, with the aim of verifying mortality from Alzheimer’s Disease in Brazil during the years 2010 to 2019, using population-based data, according to the Ministry’s Health Surveillance Secretariat (SVS/MS) from the databases of the Notifiable Diseases Information System (SINAN), where in Brazil the predominant sociodemographic characteristics were: female (64.54%), age group ≥ 80 (74.99%); white people (73.80%) and widowed people (50.66%). However, some data were ignored (9.42%), in which the gender, age, race and marital status of some patients are unknown. Thus, this work emphasizes the need for investments in public health, as this is the only way in which patients who have Alzheimer’s disease will be able to pay attention to care and adherence to treatment related to this disease.